2020
DOI: 10.48550/arxiv.2003.05823
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SAHRTA: A Supervisory-Based Adaptive Human-Robot Teaming Architecture

Abstract: Supervisory-based human-robot teams are deployed in various dynamic and extreme environments (e.g., space exploration). Achieving high task performance in such environments is critical, as a mistake may lead to significant monetary loss or human injury. Task performance may be augmented by adapting the supervisory interface's interactions or autonomy levels based on the human supervisor's workload level, as workload is related to task performance. Typical adaptive systems rely solely on the human's overall or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The speech workload algorithm was used to estimate workload in real-time during an adaptive human-machine system pilot evaluation (10 participants using the described foundational experimental design) (Heard, Fortune, and Adams, 2020) with a window size of 5s. There is no ground truth model to compare the speech-workload estimates against, due to the real-time and adaptive nature of the evaluation.…”
Section: Real-time Speech Workload Estimationmentioning
confidence: 99%
“…The speech workload algorithm was used to estimate workload in real-time during an adaptive human-machine system pilot evaluation (10 participants using the described foundational experimental design) (Heard, Fortune, and Adams, 2020) with a window size of 5s. There is no ground truth model to compare the speech-workload estimates against, due to the real-time and adaptive nature of the evaluation.…”
Section: Real-time Speech Workload Estimationmentioning
confidence: 99%
“…The effectiveness of the HotL is highly dependent upon the human multi-agent interaction mechanisms built into the system as well as the flexibility of the autonomy models. To this end, several researchers have explored techniques for exposing the intent, actions, plans and associated rationales of an autonomous agent [34], while other researchers have explored ways to improve overall performance by dynamically adapting agents' autonomy levels based on the estimated cognitive workload of the human participants; however, they also observed that frequent changes in autonomy levels reduced situational awareness and forced operators to continually reevaluate the agents' behavior [35].…”
Section: Related Workmentioning
confidence: 99%